LGG-05. MOLECULAR GUIDED THERAPY FOR A PEDIATRIC LOW GRADE GLIOMA: A CASE REPORT. (4th December 2020) - VonBergen, Jayne; Armstrong, Beth; Schmitt, Morgan
Abstract: Low grade gliomas are the most common type of central nervous system tumors among children. Despite the fact that they are not typically life threatening, low grade gliomas remain a significant clinical challenge. Case Study: Patient is a 4-year-old male who presented at 20 months of age with several weeks of ataxia, emesis, and head tilt. Imaging revealed a right temporal lobe lesion; he was subsequently taken to surgery, where a gross total resection was achieved. Imaging 9 months post resection revealed recurrent disease within the right temporal region with leptomeningeal involvement. Four months later imaging revealed progression of multifocal disease and new growth within the sella. At this time the patient started standard treatment, Carboplatin and Vincristine, per CCG 9952A. Persistent slow progression was observed despite receiving standard therapy. The patient developed a grade 3 reaction to carboplatin, worsening with each subsequent dose. At this time, he was referred to our Precision Genomics Neuro Oncology program for tumor molecular characterization. Somatic tumor testing revealed an ETV6-NTRK3 fusion, at which time standard treatment was stopped, and patient began targeted therapy, Larotrectinib. Imaging was preformed 2 months post start of targeted therapy and revealed interval decrease in size of previously enhancing nodular lesions; findings consistent with treatment response. Disease burden continues to decrease with therapy. This case illustrates a clear benefit of using molecular guided therapy in low grade gliomas.